Search for high-frequency gravitational waves with Rydberg atoms - Sugumi Kanno; Jiro Soda; Akira Taniguchi (European Physical Journal C: Particles and Fields)
Abstract We propose high-frequency gravitational wave (GW) detectors with Rydberg atoms. Rydberg atoms are ultra-sensitive detectors of electric fields. By setting up a constant magnetic field, a weak electric field is generated upon the arrival of GWs. The weak electric field signal is then detected by an electromagnetically induced transparency (EIT) in the system of the Rydberg atoms. Recently, the minimum detectable electric field with the Rydberg atoms is further improved by employing superheterodyne detection method. Hence, even the weak signal generated by GWs turns out to be detectable. We calculate the amplitude of Rabi frequency of the Rydberg atoms induced by the GWs and show that the sensitivity of the Rydberg atoms becomes maximum when the size of the Rydberg atoms is close to the wavelength of GWs. We evaluate the minimum detectable amplitude of GWs with Rubidium Rydberg atoms and find that the detector can probe GWs with a frequency $$f=4.2~\hbox {GHz}$$ f = 4.2 GHz and an amplitude around $$10^{-20}$$ 10 - 20 .